Use of health resources and healthcare costs associated with nutritional risk: The FRADEA study. Issue 4 (August 2018) - Martínez-Reig, Marta; Aranda-Reneo, Isaac; Peña-Longobardo, Luz M.; Oliva-Moreno, Juan; Barcons-Vilardell, Núria; Hoogendijk, Emiel O.; Abizanda, Pedro
Summary: Background: In spite of its high prevalence and its clinical relevance, the economic impact of malnutrition has not been sufficiently explored. Objective: To study whether malnutrition predicts total hospital healthcare costs and costs related to specialist visits, emergency department visits and hospitalization in older adults. Methods: Concurrent cohort study in Albacete City, Spain. The study sample included 827 subjects aged 70 and over from the FRADEA Study. Mini Nutritional Assessment ® -Short Form (MNA ® -SF) was recorded at baseline. Use of hospital resources (hospital admissions, emergency visits, and specialist visits), and hospital healthcare costs were recorded at follow-up. Generalized linear models (GLM) adjusted for age, sex, comorbidity, polypharmacy, and disability in basic activities of daily living were used to estimate the impact of nutritional factors on total healthcare costs per person/year (€ base year 2013) as well as specialist visit costs, emergency department visit costs and hospitalization costs. Results: The average cost associated with the use of health resources was 1922€/year. Subjects with MNA ® -SF between 0 and 7 had an average total health cost of 3492€/year, 2744€/year in those with MNA ® -SF between 8 and 11, and 1542€/year in those with MNA ® -SF between 12 and 14. Of the total health cost, 67.2% was associated with hospital admission costs. Adjusted healthcare costs were 714€/year greater in subjects with malnutrition or nutritional risk. Subjects with malnutrition or nutritional risk presented an increased adjusted risk of hospitalization (OR1.72, 95% CI 1.22–2.43). Conclusions: Malnutrition assessed by MNA ® -SF is a prognostic factor of high healthcare cost and use of resources in older adults.